An Application of Articulation Learning Models to Improve Students Learning Outcome of Geographic at SMAN I Pinggir - Iissukaesih Iissukaesih; Khairani Khairani (International Journal of Educational Dynamics, 2020)
This research begins from a problem learning process that is not the learning process which is expected, which motivated the students' attitudes about learning geography, marked by students are often late entry, is less enthusiastic in accepting the material, students do not collect the teacher's task was to provide material monotonous only discourse varied and endless value learning outcomes are still under minimum completeness criteria. The purpose of this research was to obtain data and an overview of the increasing learning outcomes of students at X IIS 5 minimum completeness criteria in SMA N I Pinggir through the Articulation learning model. This research was a classroom action research consisting of two cycles. Each cycle consists of four stages: planning, action, observation, and reflection. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student achievement has increased, in the initial condition of students completeness was only 58.82%, after conducting classroom action research, in cycle I there was an increase in learning outcomes namely completeness 76.47% and Cycle II mastery learning reached 88, 23%. The conclusion of this research is the application of Articulation learning models can improve student learning outcomes at X. IIS 5 class.